Minimally invasive surgery: only as good as the picture. - Drury, Nigel E. (Royal College of Surgeons of England, 2004)
BACKGROUND: In minimally invasive surgery, there is increased reliance on real-time 2-dimensional images. The fibre-optic light lead is one of the most frequently damaged elements of the 'imaging chain', leading to a poor quality picture. METHODS: Light leads with a honeycomb projection were connected to a light source and the resulting beam directed at a sheet of paper. Darkened sectors with diminished or absent light transmission were recorded. RESULTS: All suitable light leads in routine use were examined. A mean of 22.2% (SD 7.8%) of the projection had diminished or absent light transmission. CONCLUSION: Sub-optimal endoscopic equipment was in routine use.